PIWI‐interacting RNA MIABEPIR regulates cerebral endothelial cell function via DAPK2 pathway in offspring following maternal immune activation - Shan‐Shan Li; Miao Guo; Yao Long; Yuang Cai; Ying Zhao; Shaoyuan Huang; Houzhi Yang; Yonggang Fan; Xu Chen; Xin Jin (Clinical and Translational Medicine)
Abstract Maternal immune activation (MIA) is recognised as a risk factor in the neurodevelopmental disorders. However, the precise molecular pathways through which MIA disrupts neurovascular function remain largely unexplored. Here, we identify a novel MIA‐associated brain endothelial piRNA (MIABEPIR) involved in regulating BMEC function and BBB integrity. RNA microarray analysis of foetal brain tissue from MIA‐exposed mice revealed significant changes in piRNA expression, including a marked upregulation of MIABEPIR upregulated piRNAs. Immunofluorescence and FISH confirmed that MIABEPIR is localised in the microvascular endothelial cells of the brain. MIABEPIR overexpression enhances BMEC proliferation and angiogenesis but disrupts BBB integrity. In vivo, intracranial administration of lentiviral MIABEPIR in foetal mice resulted in marked BBB disruption. Mechanistically, we identified DAPK2 as a downstream target of MIABEPIR, leading to its downregulation. This suppression of DAPK2 inhibits autophagy in BMECs, suggesting that MIABEPIR modulates endothelial cell autophagy through the DAPK2 pathway. Our findings reveal a novel piRNA‐mediated regulatory mechanism in neurovascular function during MIA and highlight MIABEPIR's role in MIA‐induced neurodevelopmental abnormalities. Targeting the MIABEPIR‐DAPK2 axis represents a potential therapeutic strategy for addressing neurovascular dysfunction in neurodevelopmental disorders associated with maternal immune stress.